Vascular normalization and immunotherapy: Spawning a virtuous cycle - Swamy, Kumara (Frontiers in Oncology, 2022)
Anti-angiogenics, radiotherapy (especially stereotactic body radiotherapy, SBRT)/chemotherapy, and immunotherapy form a critical trimodal approach in modern cancer therapy. The normalization window, however short, is the beachhead for the strategic initiation of a decipherable disruption of cancer cells. This opening can be the opportunity for designing controlled stepwise cancer cell death (CCD) and immunological augmentation. The next step is to induce immunogenic cell death (ICD) through chemotherapy/radiotherapy concurrently with the facilitation of professional phagocytosis. Immunotherapy at this stage, when interstitial pressure decreases considerably, leads to the improved perfusion of oxygen with solutes and improved immune-friendly pH and is additionally expected to open up the tumor microenvironment (TME) for a “flood” of tumor-infiltrating lymphocytes. Furthermore, there would be enhanced interaction in “hot” nodules and the incorporation of immune reaction in “cold” nodules. Simultaneously, the added adjuvant-assisted neoantigen–immune cell interaction will likely set in a virtuous cycle of CCD induction followed by tumor cell-specific antigenic reaction boosting CCD, in turn promoting the normalization of the vasculature, completing the loop. There should be a conscious concern to protect the extracellular matrix (ECM), which will nurture the long-term immunological cross-talk to discourage dormancy, which is as essential as obtaining a complete response in imaging. The caveat is that the available therapies should be appropriately ranked during the start of the treatment since the initial administration is the most opportune period. A fast-paced development in the nanomedicine field is likely to assist in all the steps enumerated.